Ionic liquid-assisted formation of cellulose/calcium phosphate hybrid materials - Salama, Ahmed; Neumann, Mike; Günter, Christina; Taubert, Andreas (Beilstein Journal of Nanotechnology, 2014)
Cellulose/calcium phosphate hybrid materials were synthesized via an ionic liquid-assisted route. Scanning electron microscopy, transmission electron microscopy, energy-dispersive X-ray spectroscopy, X-ray diffraction, infrared spectroscopy, and thermogravimetric analysis/differential thermal analysis show that, depending on the reaction conditions, cellulose/hydroxyapatite, cellulose/chlorapatite, or cellulose/monetite composites form. Preliminary studies with MC3T3-E1 pre-osteoblasts show that the cells proliferate on the hybrid materials suggesting that the ionic liquid-based process yields materials that are potentially useful as scaffolds for regenerative therapies.
Keywords: biomineralization; calcium phosphate; carbohydrates; cellulose; hybrid materials; ionic liquid